Sex differences in the acute in vivo effects of different human SP-A variants on the mouse alveolar macrophage proteome - Phelps, David S. (2014)
Surfactant protein A (SP-A) is involved in lung innate immunity. Humans have two SP-A genes, SFTPA1 and SFTPA2, each with several variants. We examined the in vivo effects of treatment with specific SP-A variants on the alveolar macrophage (AM) proteome from SP-A knockout (KO) mice. KO mice received either SP-A1, SP-A2, or both. AM were collected and their proteomes examined with 2D-DIGE. We identified 90 proteins and categorized them as related to actin/cytoskeleton, oxidative stress, protease balance/chaperones, regulation of inflammation, and regulatory/developmental processes. SP-A1 and SP-A2 had different effects on the AM proteome and these effects differed between sexes. In males more changes occurred in the oxidative stress, protease/chaperones, and inflammation groups with SP-A2 treatment than with SP-A1. In females most SP-A1-induced changes were in the actin/cytoskeletal and oxidative stress groups. We conclude that after acute SP-A1 and SP-A2 treatment, sex-specific differences were observed in the AM proteomes from KO mice, and that these sex differences differ in response to SP-A1 and SP-A2. Females are more responsive to SP-A1, whereas the gene-specific differences in males were minimal. These observations not only demonstrate the therapeutic potential of exogenous SP-A, but also illustrate sex- and gene-specific differences in the response to it.